Understanding CATIA : a tutorial approach - Kumar, K. (Kaushik), 1968-; Ranjan, Chikesh; Davim, J. Paulo (Boca Raton : CRC Press, 2021)
"This book provides a key understanding of CATIA which is a solid modeling software. By using screen shots of step-by-step training, the reader will obtain comprehensive knowledge of all tools provided in CATIA for use in a variety of engineering fields. The book introduces CATIA basics, covers part design, discusses sheet metal design, talks about assembly, presents drawings and shows modeling an engineered component. The primary aim of this book is to assist in learning the use of CATIA software through examples taken from various areas of engineering. The content and treatment of the subject matter is most appropriate for university students studying engineering and practicing engineers who wish to learn the use of CATIA"--
Section I: Introduction Ch1: Introducing CATIA Basics Section II: Sketcher Ch2: Sketcher Workbench Ch3: Operation Toolbar Ch4: Constraints Toolbar Section III: Part Design Ch5: Part Design Section IV: Assembly Ch6: Assembly Design Section V: Drafting Ch7: Drafting Section VI: Case Study Ch8: Case Study -- 1 Ch9: Case Study -- 2 Index.
OCLC-licensed vendor bibliographic record.
Keywords: CATIA (Computer file); Computer-aided design -- Computer programs; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Computer Graphics / General; TECHNOLOGY / Industrial Health & Safety